AUDIT ON INTRAVENOUS IMMUNOGLOBULIN (IVIG) USE IN ABERDEEN ROYAL INFIRMARY NEUROLOGY DEPARTMENT ACCORDING TO 2005 ASSOCIATION OF BRITISH NEUROLOGISTS (ABN) GUIDELINES. Issue 11 (9th October 2013) - Cheripelli, Bharath Kumar; Visser, Elizabeth; Macleod, Margaret–Ann
Abstract : Background and aims: Intravenous Immunoglobulin (IVIG) is used to treat a variety of immunologically mediated neurological conditions.The Association of British Neurologists (ABN) published guidelines in 2005 for use of IVIG in neurological conditions. 1 These guidelines outline different indications for prescribing IVIG with research evidence and guidelines for monitoring patients on treatment. Our audit aimed to compare our practice in Aberdeen Royal Infirmary for the period of August 2010 to July 2011 to the ABN guidelines. We gathered data on indications of use of IVIG and 9 monitoring guidelines. Results: A total of 36 Patients received IVIG and complete data were available for analysis for 32 patients. Indications for treatment included: Guillain–Barre Syndrome (GBS) (n=10), Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) (n=8), Myasthenia Gravis (n=5), Multiple Sclerosis (MS) and Paraprotein associated neuropathy (n=2), Limbic encephalitis, Multifocal Motor Neuropathy (MMN), other CNS inflammation, Polyneuropathy, Organomegaly, Endocrinopathy, M–protein and Skin changes (POEMS) syndrome, and other demyelinating neuropathy (not CIDP) (n=1). In most of these patients other immunosuppressive treatments had been contraindicated or tried and failed, apart from the MMN group. In terms of the monitoring guidelines, we found that all patients had routine blood tests prior to the first infusion, but in nine patients pre–treatment IgA levels were not performed. 18 Patients received more than one infusion and of these ten did not have regular further pre–treatment blood tests. Informed consent was documented in only 5 patients. Out of 14 patients who had documented improvement after the first IVIG infusion, and received further infusions, four had no documented clinical deterioration prior to subsequent infusions. Only five out of the 18 patients on regular treatment had documentation on consideration of reduction in treatment dose and frequency. Intravenous Hydrocortisone and Chlorpheneramine were given as prophylaxis for allergic reactions in 17 patients before the infusion with no documented prior side effects. No patient information sheets or signed consent forms were used. The cost of IVIG was just under £0.5 million during the audit year. Outcomes: We presented these results locally and designed a protocol that includes written consent forms and patient information sheets (1). We agreed on annual consultant review dates (considering dose and frequency reduction, need for continuing IVIG use or alternative treatments) and monitoring of blood tests. We also discussed the judicious use of pre–treatment intravenous Chlorpheneramine and Hydrocortisone and consideration of oral treatment due to cost benefits where appropriate. We aim to implement the authorised protocol and close the audit cycle by repeating this in 2014.